Side Event Report. Local-based strategies to sustain food systems targeting household food and nutrition security in Vietnam - National Institute of Nutrition, Ministry of Health, Vietnam; Ministry of Agriculture and Rural Development; Alliance of Bioversity International and International Center for Tropical Agriculture (CIAT); Embassy of Canada, Vietnam (2023)
The side event "LOCAL-BASED STRATEGIES TO SUSTAIN FOOD SYSTEMS TARGETING HOUSEHOLD FOOD AND NUTRITION SECURITY IN VIETNAM in the 4th Global Conference of the One Planet Network’s Sustainable Food Systems Programme" was co-organized by the National Institute of Nutrition (NIN), under the Vietnam Ministry of Health (MOH); the Department of Cooperatives and Rural Development (DCRD), under the Vietnam Ministry of Agriculture and Rural Development (MARD); the Alliance of Bioversity International and the International Center for Tropical Agriculture (the Alliance of Bioversity and CIAT); and the Embassy of Canada in Vietnam, with support from the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT), and CGIAR Research Initiative on Securing the food systems of Asian Mega-Deltas for climate and livelihood resilience (AMD). The SHiFT research initiative is being implemented by CGIAR researchers from the International Food Policy Research Institute (IFPRI); the Alliance of Bioversity and CIAT, and the International Potato Center (CIP) in close partnership with Wageningen University and Research (WUR). The AMD research initiative is being implemented by CGIAR researchers from the International Rice Research Institute (IRRI), WorldFish, the Alliance of Bioversity, and CIAT and the International Water Management Institute (IMWI). We would like to thank all funders who supported this research through their contributions to the CGIAR Trust Fund: https://www.cgiar.org/funders/. We also would like to thank MARD for their overall logistic and financial support in making the event happen.